Non mi chiamo Francesca. Prospettive e traiettorie di giovani donne tra diaspore marocchine in Emilia-Romagna e Lombardia - Berdaouz, Ijjou; Consoli, Giulia (Antropologia Pubblica, 2024)
Arising from the convergence of an academic ethnographic research and a women-led group of social planning, the essay aims to explore the experiences, perspectives and projects of some women and girls aged between 15 and 35 whose parents have undertaken long-term mobility paths from Morocco to Italy. Aligned with previous research on Italo-Moroccan diasporas, the contribution intends to propose perspectives coming from a younger generation. The daily challenges they face in relation to diversified social arenas in the Italian public and institutional contexts are still too often alternatively silenced or amplified according to instrumental processes of exoticisation. In addition to highlighting the multifaceted quality of a hardly outlined “Moroccan diaspora”, the essay critically questions whether and at which “degrees” different conceptions of “Italianness” take shape, which expectations are possibly disappointed and how this eventually contributes to re-shape different versions of it. Narrations of the people involved reveal the intertwining of daily socio-material difficulties and the emergence of perspectives regarding their positioning in Italian society, both in Italy and abroad. The essay particularly delves into the opportunities and challenges of engaging in the Italian public spaces and discourses on one hand, and the potential for accessing, attending, or creating material spaces for alternative identity performances on the other.